Translating Paralinguistic and Onomatopoeia: An Analysis on the Novel “Bumi Manusia” by Pramoedya Ananta Toer and its Translation ”This Earth of Mandkind” by Max Lane - Erna Wiles (International Journal of English Linguistics, Literature, and Education (IJELLE), 2021)
This article is a descriptive qualitative study that aims to describe the challenges and strategies in translating paralinguistic and onomatopoeias. Data were collected from a novel by Pramoedya Ananta Toer “Bumi Manusia” and its translation “This Earth of Mankind” by Max Lane. Content and discourse analyses were performed through reductions, codings, displays, and verifications. The analyses came to a conclusion that paralinguistic (and non- linguistic) as well as onomatopoeic features are culturally bound. Ones can exist in a language community but may not in another, and the adoptions can also differ; thus, the equivalence cannot be fully maintained. Analyses on "Bumi Manusia" and its translation on its paralinguistic and non-linguistic features including onomatopoeia showed that to achieve the optimum equivalence, some steps need to be conducted. For paralinguistic and non-linguistic features two steps are needed i.e., following the target language syllabication system and adding more descriptions/illustrations on the scene to emphasize the clarity of the context; while four steps are needed to translate onomatopoeias i.e., by using onomatopoeias of the target language with the closest meaning to that of the source language, combining several onomatopoeias, lexicalizing, and using an onomatopoeia of different part of speech.Keywords: translation, paralinguistic, onomatopoeia